Expression of Cckbr, Gast, Reg1α, Tgfb1 genes in rat pancreas upon long-term hypoacidity and with administration of multiprobiotic «Symbiter® acidophilic» concentrated - Vakal, S.E.; Dvorshchenko, K.O.; Dranitsina, A.S.; Borodina, T.V.; Ostapchenko, L.I. (Вiopolymers and Cell, 2012)
Aim. Determination of the Cckbr, Gast, Reg1α and Tgfb1 genes expression in rat pancreas upon long-term hypoacidity and with administration of multiprobiotic «Symbiter® acidophilic» concentrated. Methods. Experiments were carried out on white non-strain mail rats. Hypoacidic state was modeled through intraperitoneal injection of omeprazole during 28 days. Level of genes expression was determined by semi-quantitative RT-PCR. Results. The elevation of levels of Cckbr, Reg1α and Tgfb1 mRNAs, as well as the appearance of Gast gene expression in rat pancreas upon hypoacidic conditions were shown. The levels of Cckbr and Tgfb1 mRNAs with administration of multiprobiotic «Symbiter® acidophilic» concentrated under the same conditions were similar to the control, while the expression of Gast gene was not detected; at the same time, the level of Reg1α mRNA was higher than that in animals with hypoacidity. Conclusions. Long-term hypoacidity is accompanied by changes in the expression of Cckbr, Gast, Reg1α and Tgfb1 genes in rat pancreas, while upon administration of multiprobiotic «Symbiter® acidophilic» concentrated the pattern of expression for most of the studied genes is similar to the control. Keywords: hypoacidity, pancreas, gene expression, multiprobiotics.